Marketing plan & promotional activities of prescribed drug makers: a case study of CERVARIXTM (Vaccine of Cervical Cancer) of GlaxoSmithKline Bangladesh Limited - Mamun, Md. Al (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2012.